Hubungan Tingkat Pengetahuan Pasien Dengan Perilaku Swamedikasi Terhadap Penggunaan Obat Metampiron Secara Rasional Di Apotek Guardian Summarecon Mall Bekasi Kecamatan Bekasi Utara - Indah Zahara; Prita Ardianti; Widayanti (Journal Prima Health Science, 2019)
Self medication is the act of selecting and using drugs by someone totreat a disease or symptom that can be recognized by themselves. Thatpractice is based on the thought that self medication is sufficient totreat minor ailments without involving medical staff. But in itsimplementation there are still medication error, because of that,monitoring is needed from pharmacist. Society needs appropriateknowledge to get the right behavior in self medication. Methampyronis one of the analgetic drug from nonsteroidal antiinflammatory grups(NSAID) that are included in the apothecary medicine (OWA) no. 1.This research aims to determine the correlation between knowledgewith self medication behavior towards methampyron use inpharmacies. This research is an observational analytic study withcros sectional method approach and using a purpose samplingtechnique with 88 respondents conducted in Apr – June 2019. Theresult of this research indicate that 83% of respondents have goodknowledge and 17% of respondents have sufficient knowledge. In selfmedication behavior, the use of methampyron shows 86% ofrespondents have good rationality and 14% of respondents havesufficient rationality. Where knowledge and rationality selfmedication behavior there is a significant relationship with asignificance value of 0,016 (< 0,050). From these results, it can beconcluded that the rationality behavior is closely related to theknowledge of self medication.